Alternative surgical approach to create osteomylitis in New Zealand White rabbit model - Zulkifly, Ahmad Hafiz; Abdul Aziz, Azian; Mohd Jan, Nurul Hafiza; Ibrahim, Mohd Zulfadzli (Kulliyyah of Medicine, International Islamic University Malaysia, 2015)
Introduction: The New Zealand White (NZW) rabbit is an established model for infection. Objective: An experimental protocol for local bacteria injection at distal femoral shaft to create osteomyelitis in the New Zealand White rabbit is described. Methodology: This study is a descriptive analysis of the surgical approach (and related complications) used for osteomyelitis at distal femur in the NZW model. This study was performed at Advanced Orthopaedic Research Laboratory, International Islamic University Malaysia that followed the requirements of ISO17025 standard. The procedure was to introduce sterile distilled water to wash the femoral shaft before inoculation with ATCC 25923 Staphylococcus aureus to produce osteomyelitis in the NZW rabbit. The outcomes then were analyzed through radiographic assessment and microbiology identification tests. Results: A total of 36 NZW rabbits underwent a distal femoral shaft osteomyelitis surgery. After experimental protocol established, osteomyelitis was noted and was successful infected with Staphylococcus aureus to promote osteomyelitis using the method at distal femoral shaft in all 36 NZW rabbits. We achieved 100% of inoculation of osteomyelitis in all 36 New Zealand White rabbits. No mortality noted among all rabbits involved in this study. Conclusion: This is a simple and reliable method was demonstrated and recommended for surgery via femoral shaft on New Zealand White rabbits to create osteomyelitis.